Safer prescribing of medications in adult detention - Levy, Michael; Stöver, Heino (Schriftenreihe "Gesundheitsförderung im Justizvollzug", 2013)
Prisoners are more ill than their civilian counterparts, with higher levels of addictions, mental illness, infectious diseases and dental health problems. They are intense users of precribed medications - at least while they are in custodial care. This publication brings together the experiences of 18 health professionals. Each has some experience in working with prisoner populations and each has a particular perspective on the impacts that the custodial environment has on professional practice. This publication opens opportunities for a broader appreciation of safer prescribing of medications. <engl.>